K114 Inhibits A-beta Aggregation and Inflammation In Vitro and In Vivo in AD/Tg Mice - Zhang, Yi-Hong; Mann, Dushyant; Raymick, James; Sarkar, Sumit; G. Paule, Merle; K. Lahiri, Debomoy; Dumas, Melanie; Cohen, Ashlee Bell-; C. Schmued, Larry (Current Alzheimer Research, 2014)
Alzheimer’s disease (AD) is the most common age related human neurodegenerative disorder. The major histopathological characteristics of the AD brain are extracellular amyloid-beta (Aβ) peptide loaded plaques and intraneuronal neurofibrillary tangles made of phosphorylated tau proteins. Amyloid plaques consist primarily of aggregated Aβ 1-42 and Aβ 1-40 peptides. The aim of our current study was to test novel ligands/agents with the potential to disrupt or inhibit the aggregation of Aβ peptide, specifically K114, (trans,trans)-1-bromo-2,5-bis(4-hydroxystyryl)benzene, which was initially developed as a potential positron emission tomography (PET) ligand for the in vivo detection of amyloid plaques. Systemic administration of K114 has been shown in the AD/transgenic (Tg) mouse model to be capable of crossing the blood-brain barrier (BBB) and be colocalized with amyloid plaques. In this study we determined whether K114 has the potential to inhibit Aβ aggregation in vitro in AD/Tg mice and also tested, in vivo, whether chronic daily orally administered K114 has any therapeutic potential as evidenced by inhibition or reduction of the deposits of amyloid aggregates in the brains of AD/Tg mice. Our results demonstrated that K114 strongly blocked, in vitro, the aggregation of Aβ peptide in the amyloid plaques of AD/Tg mouse brain. Systemic treatment with K114 was also effective in significantly reducing the deposits of amyloid plaques in the brains of living transgenic AD mice. Additionally, K114 significantly inhibited the typically observed plaque associated astrocytic activation, as revealed by GFAP immunohistochemistry, suggesting possible anti-inflammatory properties.
Keywords: Alzheimer’s disease